The monster's ring - Coville, Bruce; Coville, Katherine (New York : Scholastic, 2002)
A timid boy, eager to frighten the school bully on Halloween night, acquires a magic ring and the power to change himself into a hideous monster.
K
"A magic shop book."
550
K
Keywords: Monsters -- Fiction; Bullies and bullying -- Fiction; Halloween -- Fiction; Schools -- Fiction; Magic -- Fiction